A Numerical Model Comparison of the Energy Conversion Process for an Offshore Hydro-Pneumatic Energy Storage System - Andrew Borg; Tonio Sant; Daniel Buhagiar; Robert N. Farrugia; Christopher Micallef (Applied Sciences, 2023)
Energy storage is essential if net zero emissions are to be achieved. In fact, energy storage is a leading solution for reducing curtailment in an energy system that relies heavily on intermittent renewables. This paper presents a comparison between two numerical models which simulate the energy conversion unit performance of a hydro-pneumatic energy storage system. Numerical modelling is performed in PythonTM (Alpha Model) and Mathworks® Simulink® and SimscapeTM (Beta Model). The modelling aims to compare the time-series predictions for the simplified model (Alpha Model) with the more physically representative model (Beta Model). The Alpha Model provides a quasi-steady-state solution, while the Beta Model accounts for machinery inertias and friction within hydraulic flow circuits. Results show that the energy conversion performance simulations between the two models compare well, with a notable difference during system start-up due to the inclusion of transients in the Beta Model. Given its simplicity, the Alpha Model has high computational efficiency, while the Beta Model requires more computational time due to its complexity. This study showed that, despite its simplicity, the Alpha Model is able to generate results that are very similar to those from the Beta Model (with the average RMSE being less than 5%).